Management Of Character Education To Improve The Quality Of Education In Islamic Boarding School (Qualitative Study at Cipasung Islamic Boarding School and KH Zaenal Mustofa Sukamanah Islamic Boarding School in Tasikmalaya Regency) - Achmad Faruk, Agus; Suherman, Dadang; Mudrikah, Achmad; Mulyanto, Agus (International Journal of Educational Research & Social Sciences, 2022)
Islamic boarding schools are one of the educational institutions that are expected to be able to build Islamic character for all students who produce graduates who have various competencies to face various changes in today's era. legality is very much needed by both the world of work or the world of education for pesantren graduates. who have combined religious learning in pesantren with formal education and the quality of pesantren graduates is strongly influenced by the learning process in the pesantren.Therefore, Character Education in Islamic Boarding Schools is very important to balance the existing knowledge in Islamic boarding schools and schools. It is very necessary to research with a focus on character education issues, the objectives are: 1) Knowing the character education and materials developed by the Cipasung Islamic Boarding School and Sukamanah Islamic Boarding School. 2) Knowing the implementation used in the character education process developed by Cipasung and Sukamanah Islamic Boarding Schools. 3) Knowing the results of students' character education graduates who are the result of the education process in Cipasung and Sukamanah modern Islamic boarding schools. The theory that underlies this research is as follows: 1) Love of God and truth, 2) Responsibility, discipline, and independence, 3) Trust, 4) Respect and courtesy, 5) Compassion, care, and cooperation, 6) Trust self, creative, and never give up, 7) Fair and leadership spirit, 8) Kind and humble, 9) Tolerant and peace-loving. Research methods and procedures refer to Qualitative research approach. the location of the research was carried out at the Cipasung Islamic Boarding School and the Sukamanah Islamic Boarding School Tasikmalaya. The main findings of this study are. 1) The goals and materials for character education applied by the Kyai at the Islamic boarding school are Character Education in paternalistic religio education based on religious values that are based on the character of the Prophet Muhammad SAW by setting the goals and content of character education. 2) Implementation of character education developed in Islamic boarding schools, 3) Knowing the results of graduate learning that is applied is totality education by prioritizing the application of all knowledge in daily life and students' perceptions of the character education they experience in Islamic boarding schools. The implications of these findings are: 1) The objectives and materials of religious paternalistic character education by setting the goals and content of character education. 2) the implementation of character education developed in Islamic boarding schools. 3) knowing the results of graduate learning that is applied is totality education by prioritizing the application of all knowledge in everyday life and students' perceptions of the character education they experience in Islamic boarding schools.